Gut microbiota orchestrates skeletal muscle development and metabolism in germ-free and SPF pigs - Li, Zhengjie; Wen, Mingxing; Tang, Chuang; Chen, Shuangshuang; Tang, Die; Zhang, Jinwei; Sun, Jing; Ge, Liangpeng; Long, Keren; Lu, Lu; Jin, Long; Li, Mingzhou; et al. (Frontiers in Microbiology, 2025)
The gut microbiota, as a crucial symbiotic microbial community in the host, participates in regulating the host’s metabolism, immunity, and tissue development. Skeletal muscle is a key tissue for movement and energy metabolism in the body, with its development and function regulated by multiple factors; however, the molecular mechanisms by which the gut microbiota influences skeletal muscle remain unclear. This study utilized germ-free (GF) and specific pathogen-free (SPF) pig models, combined with multiple analytical approaches, to systematically investigate the effects of gut microbiota absence on skeletal muscle development, muscle fiber typing, and metabolism. The study found that skeletal muscle development in GF pigs was impaired, with significant changes in muscle fiber diameter and the proportion of type I muscle fibers, with the forelimb extensor digitorum lateralis being the most significantly affected. Metabolic analysis revealed that short-chain fatty acid (SCFA) levels in the muscles of GF pigs were reduced, while amino acid and organic acid levels were elevated, suggesting that the gut microbiota regulates muscle energy metabolism. RNA-seq analysis revealed that the expression levels of protein-coding genes (PCGs) and LncRNAs in the muscles of GF pigs were generally reduced, with LncRNAs exhibiting more pronounced dynamic changes. Differentially expressed genes were enriched in muscle development and immune pathways, with significant changes in the expression patterns of HOX and Homeobox family genes, myokines, and myosin heavy chain (MYH) subtypes. WGCNA analysis identified 16 core genes associated with muscle nutrient metabolism and nine core genes related to muscle fiber phenotypes. Cis-acting LncRNA target gene prediction identified 40 differentially expressed LncRNAs and their regulated 29 PCGs, which are primarily involved in skeletal muscle development and immune responses, suggesting that LncRNAs may influence muscle homeostasis by regulating adjacent genes. In summary, the absence of gut microbiota disrupts skeletal muscle morphogenesis, metabolic characteristics, and transcriptional regulatory networks, with LncRNAs potentially mediating the regulation of muscle-specific genes in this process. This study elucidates the interaction mechanisms between the gut microbiota and skeletal muscle, providing a theoretical foundation and data support for further exploration of the microbiota-muscle axis in pathophysiological contexts.